Balancing Exclusivity and Openness: How John Hardy Integrates Sustainability Communication into Luxury Branding - I Ketut Adi Mariana; I Ketut Gede Satya Pradana; Muhamad Hidayat (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Authentically integrating sustainable communication within the luxury industry requires more than mere polished words and certificates. The instance of John Hardy, a heritage jewelry firm based in Bali, exemplifies how legacy, location, and cultural continuity can transform sustainability from a mere marketing assertion into a tangible narrative. Internal reflections and narrative analysis indicate that selective transparency, nuanced multi-channel storytelling, and observable cultural norms enable the brand to reconcile the dichotomy of openness and exclusivity while maintaining its prestige. Daily rituals, traditional craftsmanship, and local community connections serve as evidence that enhances confidence, mitigates skepticism, and captivates varied audiences beyond superficial environmental assertions. Alignment among brand history, operational capacity, and cultural foundation is essential for credibility in sustainability communication. This study illustrates how sustainability can be seamlessly integrated into brand identity, legacy storytelling, and daily experiences, contributing to the ongoing discourse on how luxury companies should convey sustainability as an expression of continuity, locality, and engagement.